515Association between hysterectomy and risk of thyroid cancer. (2nd September 2021) - Rahman, Sabbir; Pandeya, Nirmala; Neale, Rachel; McLeod, Donald; Jordan, Susan
Abstract: Background: Hysterectomy (surgical removal of the uterus) has been consistently associated with increased thyroid cancer risk. While there may be a biologic explanation, increased ascertainment (over-diagnosis) because of greater healthcare use by women having this procedure might also contribute to the observed increased risk. We explored this association considering indications for hysterectomy, age at hysterectomy, and the potential for the association to be mediated by increased contact with health professionals or increased thyroid function testing. Methods: We recruited 730 women diagnosed with thyroid cancer and 785 age-matched population controls. We estimated odds ratios (OR) using logistic regression to assess the associations and used causal mediation analysis to investigate potential mediation. Results: Prior hysterectomy was associated with an increased thyroid cancer risk (OR = 1.55, 95% CI: 1.14-2.12). When stratified by indication for hysterectomy, the increased risk was apparent only among those who had undergone hysterectomy for bleeding disorders (OR = 1.79, 95% CI: 1.26-2.56). Additionally, the association varied by age at hysterectomy (<55 years, OR = 1.68, 95% CI: 1.22-2.31 versus ≥ 55 years, OR = 0.87, 95% CI: 0.42-1.81). Around 30% of the association was mediated by more frequent use of healthcare services. Conclusions: Hysterectomy for bleeding disorders was associated with an increased risk of thyroid cancer among women and a moderate proportion of this appeared due to frequent medical contact. Key messages: The way in which women use health services probably explains at least some of the association between hysterectomy and risk of thyroid cancer.